2016
DOI: 10.1002/pssb.201600659
|View full text |Cite
|
Sign up to set email alerts
|

Separation and optical identification of semiconducting and metallic single‐walled carbon nanotubes

Abstract: In this work we demonstrate a large‐scale separation of arc single‐walled carbon nanotubes into semiconducting and metallic fractions by an aqueous two‐phase extraction technique. The identification of nanotube conductivity type and the estimation of content for both fractions have been based on UV–vis–NIR optical absorption and time‐resolved pump–probe data. The fraction containing up to 98% of semiconducting nanotubes has been obtained. Optimization of the separation technique for the one‐step formation of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…The easiest application of ATPE is for the separation of highly enriched semiconducting SWCNT populations from the parent dispersion. 16,30,31 In my lab this is performed by competing SC with SDS for the SWCNT surface in the ATPE system, most effectively while in the presence of an oxidizing compound such as sodium hypochlorite (NaClO). In the important report of Gui et al, 35 the authors showed that addition of a small quantity of such an oxidizing agent both vastly improved robustness of the semiconducting from metallic separation delity, by effectively setting the redox potential in the ATPE system rather than relying on the ambient level, and could also enable band gap selection, critically between true metallic armchair, (n,m ¼ n), SWCNTs and the k B T level bandgap semi-metallic SWCNTs.…”
Section: Semiconducting From Metallic Swcnt Separationmentioning
confidence: 99%
“…The easiest application of ATPE is for the separation of highly enriched semiconducting SWCNT populations from the parent dispersion. 16,30,31 In my lab this is performed by competing SC with SDS for the SWCNT surface in the ATPE system, most effectively while in the presence of an oxidizing compound such as sodium hypochlorite (NaClO). In the important report of Gui et al, 35 the authors showed that addition of a small quantity of such an oxidizing agent both vastly improved robustness of the semiconducting from metallic separation delity, by effectively setting the redox potential in the ATPE system rather than relying on the ambient level, and could also enable band gap selection, critically between true metallic armchair, (n,m ¼ n), SWCNTs and the k B T level bandgap semi-metallic SWCNTs.…”
Section: Semiconducting From Metallic Swcnt Separationmentioning
confidence: 99%
“…Purification of nanotubes from byproducts was performed by tip sonication in 2 wt.% water solution of sodium cholate for 4 h and ultracentrifugation at 22 400 g. The separation of metallic and semiconducting nanotubes was made using the ATPE technique. [16] For this purpose two polymers À polyethylene glycol (6 kDa) and dextran (70 kDa), and two types of surfactants À sodium dodecyl sulfate and sodium cholate in appropriate concentrations were used. It is worth noting that separation of SWCNTs with such a large average diameter by ATPE technique was demonstrated for the first time here.…”
Section: Swncts Samples Preparationmentioning
confidence: 99%
“…It is worth noting that separation of SWCNTs with such a large average diameter by ATPE technique was demonstrated for the first time here. The purity of obtained semiconducting and metallic fractions was estimated to 98%, [16] according to optical absorbance spectra (Figure 1). After sorting, SWCNTs were purified from residual polymers and surfactants by adding sodium chloride and ethanol to the suspension and ultracentrifugated at 360 000 g for 15 min in order to deposit the nanotubes.…”
Section: Swncts Samples Preparationmentioning
confidence: 99%
“…Much effort has been put into chirality selective chemical vapor deposition (CVD) synthesis of SWCNTs . Significant progress was achieved in developing various SWCNT sorting methods . However, controlling simultaneously chirality of produced nanotubes and morphology of nanotube assembly is still a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] Significant progress was achieved in developing various SWCNT sorting methods. [12][13][14][15][16][17][18] However, controlling simultaneously chirality of produced nanotubes and morphology of nanotube assembly is still a challenging task. One of the ways to obtain the desired level of the SWCNT structure control is a vapor-phase epitaxial (VPE) growth method.…”
Section: Introductionmentioning
confidence: 99%